2009
DOI: 10.1002/pssc.200880959
|View full text |Cite
|
Sign up to set email alerts
|

Milliwatt power 270 nm‐band AlGaN deep‐UV LEDs fabricated on ELO‐AlN templates

Abstract: We demonstrated CW milliwatt power operations of 270 nm‐band AlGaN multi‐quantum well (MQW) deep‐ultraviolet (DUV) light‐emitting diodes (LEDs) fabricated on epitaxial lateral overgrowth (ELO) AlN templates on sapphire. An initial AlN stripe layer was grown directly on sapphire by using ammonia (NH3) pulse‐flow multilayer (ML) growth method. An AlN stripe structure with a width of 5 μm and a spacing of 3 μm was completely coalesced after the growth of an approximately 15 μm‐thick ELO‐AlN layer grown by low‐pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 15 publications
0
14
1
1
Order By: Relevance
“…1(b). It is found that the AlN epilayer has completely coalesced in a thickness about 3 μm, which is less than the previously reported coalescence thickness for AlN grown on micro-stripe patterned substrates via ELO technique412. It should be ascribed to the nano-scale patterns on the substrate and the effective control of the AlN lateral growth.…”
Section: Resultscontrasting
confidence: 55%
“…1(b). It is found that the AlN epilayer has completely coalesced in a thickness about 3 μm, which is less than the previously reported coalescence thickness for AlN grown on micro-stripe patterned substrates via ELO technique412. It should be ascribed to the nano-scale patterns on the substrate and the effective control of the AlN lateral growth.…”
Section: Resultscontrasting
confidence: 55%
“…As compact solid-state devices, DUV LEDs have many advantages over the traditional mercury lamp, and are deemed as the future UV light source. Nevertheless, compared with the great success of InGaN-based blue LEDs, the present performance of AlGaN-based DUV LEDs is still far from satisfactory though some progress has been made [3][4][5][6][7]. AlGaNbased DUV LEDs have been mostly grown on sapphire substrates.…”
Section: Introductionmentioning
confidence: 98%
“…[72,[77][78][79] Significant reduction in TDD was observed in the areas between ridges. A maximum output power of 2.7 mW under CW operation of 273 nm DUV LEDs on ELO AlN templates with the wing region having TDD of 3×10 8 cm -2 has been reported by Hirayama et al [80] By reducing the TDD in AlN layers on sapphire from 10 10 cm −2 to 10 9 cm −2 , output powers of 1mW and about 4mW for 295 nm and 324 nm LEDs, respectively, have been demonstrated by Kueller et al [69] This method has also been applied for growing AlN template on Si (111) substrate, as illustrated in Figure 7. ELO AlN templates on Si (111) substrate with FWHM values of 920 and 780 arcsec for XRD ω-rocking curves from the (0002) and (101 1) reflections, respectively, with simultaneous reduction in crack density have been achieved by Zhang et al [81] A peak pulsed power and slope efficiency of ~0.6 mW and ~1.3 mW/mA, respectively, were demonstrated for 359 nm UV LEDs after removing the Si (111) substrate.…”
Section: Epitaxial Lateral Overgrowth Of Aln and High Al-molar Fractimentioning
confidence: 79%